STRATEGI PELAYANAN PADA INDUSTRI RITEL DALAM MEMPERTAHANKAN KESETIAAN PELANGGAN (Studi Pada Pengusaha Ritel Modern Sumber Alfaria Trijaya Tbk Di Lampung Timur) - Pipit Afifah (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Every retail entrepreneur in East Lampung is required to be able to satisfy customer aspects by assessing the desires, needs and expectations of customers to the market. The strategy carried out by modern retailers is the fact that customers who are not satisfied for the goods or services they have consumed will look for suppliers of goods or services from the other companies. The problems faced in this modern retail business are strategies to attract customers who are used in the modern retail industry of Alfamart and Indomaret still use the same system, by way of maximal service, because it must be in accordance with the wishes of consumers. We must be able to be friendly to attract customers, so that customers are able to survive in all of these retail industries.Keywords: Service Strategy, Customer Loyalty